Pengembangan Lembar Kerja Peserta Didik Berbasis Kearifan Lokal Untuk Meningkatkan Keterampilan Berpikir Kritis - Yosi Arfika; Astuti Wijayanti; Handoyo Saputro (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2020)
Local wisdom-oriented learning invites students to gain direct learning experience with natural situations. This study aims to describe how to develop LKPD based on local wisdom that is appropriate to be used to improve the critical thinking skills of eighth grade junior high school students. This research includes development research using 4-D development models namely Define, Design, Develop and Dessiminate. The LKPD research instrument was in the form of a questionnaire that included several aspects of assessment. The LKPD validation was carried out by media experts, material experts, peer reviewers, science teachers and grade VIII students. The results of this study indicate that the local wisdom-based science worksheet developed with the 4-D model to improve critical thinking skills of junior high school students in grade VIII is declared feasible or valid based on the validator's assessment. Assessment of media experts with a percentage of ideals of 80%, according to expert material 86.08%, percentage of ideals according to peer reviewers 92.06%, science teachers of SMP 5 Banguntapan 80%, teachers of SMP 2 Godean 88.75%, while according to students of SMP 5 Banguntapan was 82.28%, while the students of Godean 2 Junior High were 81.90%. Based on the assessment of the science-based LKPD of local wisdom in order to improve the critical thinking skills of eighth grade junior high school students who are deemed fit for use in science learning